Ekonomi Politik Komodifikasi Media Digital: Influencer Anak di YouTube - Soegiarto, Andrea (Kinesik, 2025)
The political economy of media has evolved into a practice that spans various aspects of life. Digital media platforms serve as channels for economic powers to influence consumer behavior for profit maximization. This study examines how children become commodified as workers in the digital media culture industry through the phenomenon of Kid Influencers on YouTube. Using qualitative methods and a political economy perspective, this research analyzes the Ryan's World and Super Duper Ziyan YouTube channels. Data collection involved analyzing previous research on Kid Influencers and gathering information from popular children's YouTube channels. The results indicate that YouTube's ability to reach targeted audiences enables children to become objects of worker commodification, as monetization creates economic exchange value. This study reveals how capitalism infiltrates media, utilizing social platforms to expand business opportunities through content featuring children for child consumption.